Signal processing in intelligent control systems for low-visibility and low-mobility air units - Solonskaya, S.; Zhyrnov, V. (Radiotekhnika, 2018)
It is proposed to improve the effectiveness of survey radars in detecting and recognizing low-visible and slow-moving air objects by creating special (virtual) space-time images for accumulating both energy and semantic components of signal information using the mathematical apparatus of algebra of finite predicates. It is shown how this approach can be used to detect and recognize slow-moving aircraft, which can be both in flight mode and in hang mode. Such signaling information will be accompanied by different semantic distinctive features: a sign of a trace and  sign of the signal repetition.